2005
DOI: 10.3748/wjg.v11.i18.2768
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of cytokines polymorphisms with autoimmune hepatitis and primary biliary cirrhosis in the Chinese

Abstract: The polymorphisms of IL-1RN and IL-6 -174G/C appear to be associated with PBC in Chinese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…Each had two alleles (-592C/A, -819C/T, and -1082G/A), and a strong allelic association between sites -592 and -819 was discerned, in that the combinations -592CC and -819CC, -592CA and -819TC, and -592AA and -819TT always occurred at the same time. The -1082 GG genotype was not observed, which is consistent with a previous study (Fan et al, 2004). There were no significant differences regarding sex and age of carrier between the genotypes of the three polymorphisms (P > 0.05).…”
Section: Il-10 Gene Polymorphismsupporting
confidence: 91%
“…Each had two alleles (-592C/A, -819C/T, and -1082G/A), and a strong allelic association between sites -592 and -819 was discerned, in that the combinations -592CC and -819CC, -592CA and -819TC, and -592AA and -819TT always occurred at the same time. The -1082 GG genotype was not observed, which is consistent with a previous study (Fan et al, 2004). There were no significant differences regarding sex and age of carrier between the genotypes of the three polymorphisms (P > 0.05).…”
Section: Il-10 Gene Polymorphismsupporting
confidence: 91%
“…The latter group, however, more recently described an association of PBC with the IL1-RN intron genotype comparing frequencies in 77 patients with PBC and 160 controls. 63 Further, based on experimental evidence of cytokine profiles and its involvement in the development of T helper 1 (Th1) cell responses, SNPs of the promoter region of the IL-10 gene were also analyzed in patients with PBC and controls. 55,63,64 Data from Italian and Japanese series demonstrated that both groups presented a higher prevalence of the À1082G/G genotype.…”
Section: Mhc and Pbcmentioning
confidence: 99%
“…63 Further, based on experimental evidence of cytokine profiles and its involvement in the development of T helper 1 (Th1) cell responses, SNPs of the promoter region of the IL-10 gene were also analyzed in patients with PBC and controls. 55,63,64 Data from Italian and Japanese series demonstrated that both groups presented a higher prevalence of the À1082G/G genotype. 64 Such association was not confirmed in 77 Chinese patients with PBC.…”
Section: Mhc and Pbcmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the disease associations demonstrated in the HLA region, preliminary studies have implicated the involvement of non-HLA loci with susceptibility to AIH. These include the immune modulator cytotoxic T lymphocyte antigen-4, 58 proinflammatory cytokines, 59 Fas, 60 and CD45. 61 Further study is needed to confirm these associations.…”
Section: Paradigms Of Rare Complex Liver Diseasesmentioning
confidence: 99%